2014
DOI: 10.17219/acem/37361
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Patients’ Quality of Life

Abstract: Patients suffering from head and neck cancers often require a multidisciplinary approach before and after surgery. Restoration of facial esthetics, speech, mastication and others often requires a long-lasting, divided rehabilitation. Quality of life (QOL) is measurable in a patient's life before and after surgery and complete treatment. The state of QOL has different parameters depending on the patient's clinical diagnosis, type of treatment and surgeries performed. In this paper, the authors are focusing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
2
18
0
1
Order By: Relevance
“…physical functioning and nutrition [4]. An important aspect of such side effects are the challenges met by patient with HNC related to eating ability, weight loss and changed meaning of food [5], but the picture is further complicated by the large symptom burden identified also before treatment is initiated [6].…”
Section: Introductionmentioning
confidence: 99%
“…physical functioning and nutrition [4]. An important aspect of such side effects are the challenges met by patient with HNC related to eating ability, weight loss and changed meaning of food [5], but the picture is further complicated by the large symptom burden identified also before treatment is initiated [6].…”
Section: Introductionmentioning
confidence: 99%
“…Special and individual protocols should also be assessed in patients with TS. 19 The results of our research indicate that life satisfaction can be affected by both health-related and demographic variables. Our study revealed lower quality of life in those women with Turner syndrome who were troubled by their short statures, loneliness, feeling of being handicapped, and negative attitudes of other people.…”
mentioning
confidence: 69%
“…SCCHN, as a common malignant tumor of the head and neck, is characterized by a high degree of malignancy, high incidence of recurrence and metastasis, and high mortality. The combined treatment consisting of surgery or radiotherapy with postoperative adjuvant chemotherapy exhibits an improved outcome to prolong the overall survival in the treatment of SCCHN, but the prognosis remains far from optimistic due to the complexity and inscrutability of SCCHN (14,15). Development of novel effective therapeutic strategies is urgent to improve life quality and reduce quantity of patients with recurrent or metastatic SCCHN.…”
Section: Discussionmentioning
confidence: 99%